PERTIMBANGAN HAKIM DALAM PENJATUHAN PIDANA DI BAWAH MINIMUM KHUSUS PERKARA NARKOTIKA: PUTUSAN NOMOR 215/PID.SUS/2020/PN.JTH - Nurul Aulia Fitri; Muhammad Rustamaji (Sebelas Maret University, 2021)
This article aims to analyze the judge's considerations in imposing a sentence below the special minimum for narcotics crime cases by studying the decision of the Jantho District Court Number 215/Pid.Sus/2020/Jth which violates the special minimum criminal provisions in Law No.35 of 2009 concerning Narcotics. This research method is a prescriptive normative legal research with a case approach. Based on the research conducted by the author, it was found that in imposing a sentence below the special minimum in the narcotics crime case committed by T. Irfan, the judge made juridical and non-juridical considerations accompanied by the application of combined sentencing theory. This consideration is based on the fulfillment of the elements of the second alternative indictment, the fact that the purpose of possession of narcotics is for self-consumption, the provisions of the SEMA which accommodate the doubts of judges to then be able to commit deviations, and are based on the ability to be responsible, mitigating and aggravating things. The considerations in imposing the sentence are in accordance with legal objectives which are based on legal justice, legal benefits and legal certainty. From the results of this study it can be concluded that the use of articles regarding the possession and control of narcotics is irrelevant because they are always associated with the purpose of use and distribution which are regulated in different provisions so that these provisions seem ambiguous and need to be corrected.Keyword: Judge’s Consideration; Narcotics Crime; Special Minimum Punishment